ChAMP: updated methylation analysis pipeline for Illumina BeadChips - Tian, Yuan; Morris, Tiffany J; Webster, Amy P; Yang, Zhen; Beck, Stephan; Feber, Andrew; Teschendorff, Andrew E (Bioinformatics (Oxford, England), 2017)
The Illumina Infinium HumanMethylationEPIC BeadChip is the new platform for high-throughput DNA methylation analysis, effectively doubling the coverage compared to the older 450 K array. Here we present a significantly updated and improved version of the Bioconductor package ChAMP, which can be used to analyze EPIC and 450k data. Many enhanced functionalities have been added, including correction for cell-type heterogeneity, network analysis and a series of interactive graphical user interfaces. ChAMP is a BioC package available from https://bioconductor.org/packages/release/bioc/html/ChAMP.html. a.teschendorff@ucl.ac.uk or s.beck@ucl.ac.uk or a.feber@ucl.ac.uk. Supplementary data are available at Bioinformatics online.